MOTIVASI INTRINSIK PEMBERIAN ASI EKSLUSIF PADA IBU YANG BEKERJA DI DESA TEJA TIMUR KECAMATAN PAMEKASAN KABUPATEN PAMEKASAN - Rahayu Yuliana Watiningrum; Anggeria Oktavisa Denta; Nur Faridatul Hasanah (Indonesian Health Science Journal, 2023)
Introduction: Exclusive breastfeeding is the best first and main food for babies aged 0-6 months in meeting the nutritional needs and growth and development of babies. One of the factors in the failure of exclusive breastfeeding is the influence of socio-culture where the mother's activities or work outside the home causes the mother to be unable to share her time between giving exclusive breastfeeding and breastfeeding her baby. The purpose of this study was to determine the intrinsic motivation of exclusive breastfeeding for working mothers. Methods: The design used in this study used descriptive, non-probability type total sampling techniques with a population of 15 working mothers who had babies aged 0-6 months. Data was taken by using a questionnaire. The results of data analysis are presented in the form of tables and narratives. Results: Research shows that most of the 60% or 9 respondents are categorized as high and none of 0% or 0 respondents is categorized as low.Conclusion: Based on the Results of the study, it can be concluded that most mothers work in East Teja Village have high motivation in providing breast milk.